Topical steroid abuse on face: a prospective study from a tertiary care centre of north India - Nyati, Asha; Singhal, Anil Kumar; Yadav, Devendra; Sharma, Manoj Kumar (International Journal of Research in Dermatology, 2017)
Background: Topical corticosteroids (TCS) are widely misused on face which is associated with significant adverse effects and poor awareness of these effects. The aim of this study was to assess the frequency of misuse of topical corticosteroids, the causes behind it and the most common adverse events resulting from it and to make aware the people about it Methods: This study was conducted at Dermatology Department of Govt. Medical College, Kota during period of one year from July 2015 to June 2016. A total of 670 patients using topical steroids over face were enrolled in the study. Details about the usage of topical corticosteroids and their side effects were recorded. Results: Majority of the patients were females (72.68%). The most common reason for misuse was melasma (57. 91%) followed by use as a fairness cream (22.38%). Most of the patient used topical steroid cream for duration of 3-6 months (33.13%). Most common age group was 21-30 years (48.20%). Acne form eruption (38.05%) and rebound erythema (28.20%) were the most common adverse effects noted. Patients were ignorant of the ingredients and their side effects. Conclusions: Steroids have been misused by patients on their own or by pharmacist and non-dermatologist physicians for various reasons. Topical steroid should not be used on the face unless it is under strict dermatological supervision.